2016
DOI: 10.12944/cwe.11.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Is that Environmental Factor Affected the Distressed Farmers’ most!? - An Exploratory Factor Analysis of Constraint and Amelioration Strategies in National Calamity Hit Region of India

Abstract: The Kosi River is infamous in India for its rapid and recurrent changes of course and the widespread flood damages it causes almost annually. But, the flood of 18th August, 2008 was the most devastating down the memory lane of the survival. The destruction was of such a magnitude that state government of Bihar had to seek World Bank (Project ID: P122096) assistance. Keeping this in view, an earnest effort was made to study the perceived constraints of distressed farmers and strategies for its amelioration. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…So, the respondents were fi rst asked to rank the particular constraint. The order of merit thus given by the respondents was converted into percent position by using the formula as used by Lal et al (2016):…”
Section: Methodsmentioning
confidence: 99%
“…So, the respondents were fi rst asked to rank the particular constraint. The order of merit thus given by the respondents was converted into percent position by using the formula as used by Lal et al (2016):…”
Section: Methodsmentioning
confidence: 99%
“…Constraints analysis is very prevalent in survey-based research as Lal et al, (2016b) through exploratory factor analysis (EFA) explored 4 latent broad constraints having Eigen value >1, which was rechristened as: environmental, pecuniary, policy and miscellaneous constraints. Moreover, responses of the dairy farmers on extent of severity of constraints faced after national calamity was expounded by Lal et al, (2016a) by using Friedman test and it statistically identified that the most severe broad constraints perceived by dairy farmers was "technical constraints" followed by "economical constraints", "physical constraints", and "social constraints".…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%
“…13 There are 4 broad steps in conducting a case study 11,14 explained in Figure 2. Interview schedule method is widely adopted primary data collection tool [2][3][4][5][6][7] and was used to figure out and prioritize the benefits gained by the intervention. Benefits analysis is common in extension study to know the results of any intervention.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Benefits analysis is common in extension study to know the results of any intervention. The ranking procedure followed may be different for measuring perceived benefits viz., Garrett's ranking method, 6,15 mean score ranking procedure, 4 and Alfares ranking procedure. 3,16 To determine the ranking in Alfares model least-squares regression was applied to S n versus n: n 37.75756 S 3.19514 n + = Therefore, for any set of n ranked benefits (in the present manuscript n represents 4 benefits), assuming a weight of 100 percent for the first-ranked benefit, the percentage weight of benefits ranked as r is given by: Standardized Multivariate Regression Analysis 17 and Polytomous Universal Model.…”
Section: Data Collection Toolmentioning
confidence: 99%
See 1 more Smart Citation